PENGARUH DPK, NPF DAN ZPR TERHADAP PROFITABILITAS DENGAN FDR SEBAGAI MODERASI - Sari, Winda Novita; Bawono, Anton (Al-Qashdu : Jurnal Ekonomi dan Keuangan Syariah, 2023)
Based on the phenomenon regarding the development of Return on Assets (ROA) in Islamic banking in Indonesia in recent years, which shows the occurrence of fluctuations in developments and descriptions of what factors influence the financial performance of Islamic banking based on existing theory, there is an inconsistency in this research, namely the use of the moderating variable, namely Financing to Deposit Ratio (FDR), to see the relationship between DPK, NPF, and ZPR on ROA. The results of this study show that DPK has a negative and significant effect on the profitability of Islamic commercial banks. Non-performance financing has a negative and insignificant effect on the profitability of Islamic commercial banks. ZPR has a negative and insignificant effect on the profitability of Islamic commercial banks. This is caused by the fact that most Islamic commercial banks payments of zakat are not yet perfect, namely 2.5% of their assets, which have reached the ratio. Or even not paying zakat at all. and for the variable financing deposit ratio, it is able to moderate the effect of DPK and NPF on the ROA of Islamic Commercial Banks. However, the financing deposit ratio variable is not able to moderate the effect of ZPR on the ROA of Islamic commercial banks. Which means FDR is not a moderating variable on the effect of ZPR on the ROA of Islamic commercial banks.Keywords: Profitability; ZPR; FDR